Kajian Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) PT. X - Berliana, Putri Nadia; Restu Hikmah Ayu Murti; Wahyu Dwi Utomo (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
PT.X is a branch of the industry engaged in agribusiness that provides agricultural products and services. The production process carried out by PT. X results in a product and other production process that can no longer be used or discarded. B3 waste is the residue of a company and/or activity which because of its nature and/or concentration and/or amount contains hazardous and/or toxic substances which directly or indirectly pollute the environment, human health and can endanger the survival of other living things. The purpose of this research is to know and understand the B3 waste management system and to implement an evaluation of the B3 waste operating system. Data collection through observation in the form of a general introduction to the location and direct field orientation by PT. X offline. Data processing and analysis was carried out by comparing the existing conditions of the B3 waste treatment carried out by PT. X with applicable regulations. Research variables include reduction, packaging and storage, as well as the use of B3 waste management. The results of the study show the compatibility between the application of B3 waste management at PT. X and the regulations in force largely comply with this.